Risiko Kebangkrutan Pada Perusahaan Bank Umum Swasta Nasional Yang Terdaftar Di Bursa Efek Indonesia - Bambang Budhijana; Nelmida Nelmida (Jurnal Akuntansi Keuangan dan Bisnis, 2018)
ABSTRACTThis study employ to determine the risk of bankruptcy of National Commercial Banks listed on the Indonesia Stock Exchange. The data used is secondary data from the company's financial statements repots 2011-2015. The population of this research is all National Commercial Banks listed on Indonesia Stock Exchange with sampling technique purposive sampling. The method of analysis used in this research is Z Score Model. Based on the results of Z Score Model analysis that there are eleventh banking companies that belong to the category of Safe Zone with Z Score value > 2.60, onece of company  banking category including Gray Zone with the value is  Z Score 1.1 < Z<  2.60, and two companies which includes a Distress Zone with Z Score value <1.1.